The punk rock politics of Joe Strummer : Radicalism, resistance and rebellion - Gall, Gregor (Book collections on Project MUSE., 2022)
Drawing on Strummer's lyrics, interviews and bootleg recordings, as well as interviews with friends and contemporaries like Billy Bragg, The punk rock politics of Joe Strummer reveals the wide-ranging political influence of one of the twentieth century's iconic rock'n'roll rebels.